PERILAKU BERLANJA ONLINE MAHASISWA DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Nizar, Wulandari; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Simpang Baru Village, Tampan Sub-district, Pekanbaru City. The purpose of this study is to determine the behavior of student consumption in online shopping in Simpang Baru Village Tampan Sub District Pekanbaru City. The focus of this research is to know what factors affect the behavior of students online at Simpang Baru Village Kecamatan Tampan Pekanbaru City. Sampling technique purposive sampling technique. and set the number of samples as many as 50 people. The author uses quantitative descriptive method and Instrument data is the observation and questionnaire. The research found there are some student consumption behavior in online shopping in Simpang Baru Village, that is: Pamer, research found that 66% of students only buy good quality goods with high selling value only. Boros, Research found that 48% of students feel not enough with the allowance provided by his parents. Having fun, the study found that 26% of students in Simpang Baru Village who are behaving online say they sometimes shop online because of their unique packaging. Span of time, Research found that 40% of college students stated sometimes buy the same item in different months. Studin found that there are several factors that influence student shopping behavior in new Simpang Village, namely: Culture, Research found that 62% of students declare their choice in interacting with peers. Social, Research found that 64% of students said they liked friends who had the same online taste so they could exchange ideas. Psychology, Research found that 66% of college students said online shopping behaviors improved their moods by shopping online they were happy instantly when looking at items in post. Personally, the study found that 66% of college students said they were never rebuked in online shopping behavior, this is because they feel grown and parents no longer need to curb them in action. Keywords: Behavior, Consumptive, Student